2022
DOI: 10.1039/d2tc03199j
|View full text |Cite
|
Sign up to set email alerts
|

Half-metallic double perovskite oxides: recent developments and future perspectives

Abstract: The continuous miniaturization of the charge-based electronic devices and overcoming the bottleneck of Moore's law, have driven the rapid growth of spintronics, which operates the freedom of electronic spin rather...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 257 publications
0
19
0
Order By: Relevance
“…7,8 As a consequence, DP oxides find potential applications in room-temperature (RT) spintronics because of their half-metallic ferromagnetism, high magnetic Curie temperature (T C ) well above RT, and large tunneling magnetoresistance (TMR). 9,10 For instance, in 1998 Kobayashi et al first reported on the high TMR of an ordered Sr 2 FeMoO 6 (SFMO) DP oxide with T C = 415 K. 11 The TMR value was achieved at 42%@4.2 K and 7 T and 10%@300 K and 7 T. The saturation magnetization (M S ) of the ordered SFMO oxide is theoretically evaluated to be 4.0 μ B /f.u. based on an ionic spin-only picture where Fe 3+ and Mo 5+ ions are antiferromagnetically coupled at B-site.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 As a consequence, DP oxides find potential applications in room-temperature (RT) spintronics because of their half-metallic ferromagnetism, high magnetic Curie temperature (T C ) well above RT, and large tunneling magnetoresistance (TMR). 9,10 For instance, in 1998 Kobayashi et al first reported on the high TMR of an ordered Sr 2 FeMoO 6 (SFMO) DP oxide with T C = 415 K. 11 The TMR value was achieved at 42%@4.2 K and 7 T and 10%@300 K and 7 T. The saturation magnetization (M S ) of the ordered SFMO oxide is theoretically evaluated to be 4.0 μ B /f.u. based on an ionic spin-only picture where Fe 3+ and Mo 5+ ions are antiferromagnetically coupled at B-site.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Following this work, much efforts have been devoted to the family of ordered DP oxides to find the possible new potential candidates for RT spintronics. 9,14,15 In the family of A 2 B′B″O 6 DP oxides, their magnetic properties are governed by the exchange and superexchange interactions via the B′(t 2g )-O(2p)-B″(t 2g ) magnetic path. A wide range of physical properties of DP oxides can be achieved by suitable combinations of the B′ and B″ ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These have attracted attention due to their ability to accommodate an extensive range of rare earth elements at the A-site, signicantly modifying the bond length and bond angle of the octahedra, and two different types, sizes and valence states of cations at the B ′ and B ′′ -sites, offering the opportunity to manipulate, tune and tailor their physical properties according to industrial and technological needs. 7,8 ODP usually exhibit half-metallic (HM), 9,10 ferrimagnetic (FiM), 11,12 ferromagnetic (FM), 13,14 antiferromagnetic (AF), 15,16 half-metallic ferromagnetic (HM-FM), 17,18 half-metallic ferrimagnetic (HM-FiM), 17,19 nonmagnetic (NM), 18,20 ferroelectric (FE), 12,21 and semiconducting (SC) 12,18,21 responses near room temperature. Halfmetallic materials have well-dened band gaps in one spin state and metallic bands in the other spin channel.…”
Section: Introductionmentioning
confidence: 99%
“…21 Thus, HM materials have quantization of magnetic moment, zero spin susceptibility and 100% spin polarization at the Fermi level. [21][22][23] HM materials have potential application in data storage memory and magnetic recording due to their single spin charge carriers. 24,25 J.…”
Section: Introductionmentioning
confidence: 99%